Association between blood urea nitrogen to serum albumin ratio and in-hospital mortality of patients with sepsis in intensive care: A retrospective analysis of the fourth-generation Medical Information Mart for Intensive Care database - Cai, Shaoyan; Wang, Qinjia; Chen, Chao; Guo, Chunming; Zheng, Liangjie; Yuan, Min (Frontiers in Nutrition, 2022)
Background: This study aimed to investigate the relationship between the blood urea nitrogen to serum albumin ratio (BAR) and in-hospital mortality in patients with sepsis. Methods: This is a retrospective cohort study. All septic patient data for the study were obtained from the intensive care unit of Beth Israel Deaconess Medical Center. Adjusted hazard ratios (HR) and 95% confidence intervals (CI) were calculated using multivariable Cox regression analyses. Survival curves were plotted and subgroup analyses were stratified by relevant covariates. Results: Among 23,901 patients, 13,464 with sepsis were included. The overall in-hospital mortality rate was 18.9% (2550/13464). After adjustment for confounding factors, patients in the highest BAR quartile had an increased risk of sepsis death than those in the lowest BAR quartile (HR: 1.42, 95% CI: 1.3–1.55), using BAR as a categorical variable. When BAR was presented as a continuous variable, the prevalence of in-hospital sepsis-related death increased by 8% (adjusted HR: 1.08, 95% CI: 1.07–1.1, P<0.001) for each 5 unit increase in BAR, irrespective of confounders. Stratified analyses indicated age interactions (P<0.001), and the correlation between BAR and the probability of dying due to sepsis was stable. Conclusions: BAR was significantly associated with in-hospital mortality in intensive care patients with sepsis. A higher BAR in septic patients is associated with a worse prognosis in the ICU in the USA. However, further research is required to confirm this finding.